PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN PENGETAHUAN KARYAWAN BAGIAN AKUNTANSI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DENGAN PELATIHAN SEBAGAI VARIABEL KONTROL - Netty Febrianingsih (Universitas Slamet Riyadi, 2015)
The porpose of this study was 1) to analyze utilization of information technology influence effectiveness of accounting information system. 2) to analyze accounting employees knowlage influence effectiveness of accounting information system. 3) to analyze accounting employees knowlage viewed from training influence effectiveness of accounting information system. There wer 20 respondens accounting. In this research was quantitative method used primary data. The data collected was decumentation method, interviews, questionnaires. The analyze method of this research that used was multiple regressions. The results showed that 1) untilization of information influence take affect influence effectiveness of accounting information system. 2) accounting employees knowlage no affect influence effectiveness of accounting information system. 3) accounting employees knowlage viewed from training no effact effectiveness of accounting information system. Keywords: untilization of information technology, accounting employees knowlage, training, effectiveness of accounting information system.